Scrophularia koraiensis, a new synonym to Scrophularia kakudensis (Lamiales: Scrophulariaceae) - Wang, Ruihong; Wang, Dandan; Qi, Zhechen; Li, Pan; Fu, Chengxin (Phytotaxa, 2015)
Scrophularia Linnaeus (1753: 619), is one of the largest genera of Scrophulariaceae, includes about 270 exant species, and is predominantly distributed in Holarctic regions of both the Old and New World (Olivencia, 2009; Olivencia & Devesa, 1993). Scrophularia koraiensis was first described by Nakai (1909) based on material collected in mount Kum-gang san, Kang-uön, Korea and considered as an endemic medicinal plant of Korea (Han et al. 2003). S. koraiensis was characterized by having petiole 4 to 7 cm long, blade ovate–lanceolate, 10 to 15 cm long, terminal or axillary cymes, pedicels glandular hairy and ovate capsule (Nakai 1909).